Dynamics of the Islamic Political Movement : The Influence of Pesantren's Islamic Community in East Java in the 2024 Elections - Pramuja Yudha Pratama Pratama; Muhammad Badri Habibi Habibi; Ratih Kusuma Ningtias (Peradaban Journal of Religion and Society, 2024)
This article seeks to examine the dynamics of the Islamic political movement in East Java, with a specific emphasis on the influence wielded by the Islamic community originating from pesantren in the context of the 2024 General Election (Pemilu). Employing a qualitative approach and drawing upon data from relevant literature and current media sources related to the election year, this research scrutinizes the active role of pesantren communities in shaping and influencing the political opinions of the Islamic community in East Java. The analysis conducted encompasses significant factors such as fatwas issued by religious scholars, political education within pesantren, and the influence of religious figures who play a pivotal role in shaping the political views and preferences of Islamic voters. Concurrently, this article also delves into how the pesantren community interacts, both through collaboration and competition, with other political groups to sway the outcomes of the 2024 General Election. The findings of this article suggest that the loyalty of Santri voters and pesantren, with their unwavering allegiance, surpasses that of Abangan and nationalist groups. Therefore, the role and influence of the Islamic community from pesantren in East Java occupy a significant and influential position in the dynamics of politics during the 2024 General Election. Artikel ini bertujuan untuk mengkaji dinamika gerakan politik Islam di Jawa Timur, dengan penekanan khusus pada pengaruh yang dimiliki oleh komunitas Islam yang berasal dari pesantren dalam konteks Pemilihan Umum 2024. Dengan pendekatan kualitatif dan menggunakan data dari literatur relevan serta sumber media terkini terkait tahun pemilihan, penelitian ini mengulas peran aktif komunitas pesantren dalam membentuk dan memengaruhi opini politik komunitas Islam di Jawa Timur. Analisis yang dilakukan melibatkan faktor-faktor signifikan seperti fatwa yang dikeluarkan oleh ulama, pendidikan politik di pesantren, dan pengaruh tokoh agama yang memainkan peran kunci dalam membentuk pandangan politik dan preferensi pemilih Islam. Secara bersamaan, artikel ini juga menjelajahi bagaimana komunitas pesantren berinteraksi, baik melalui kolaborasi maupun kompetisi, dengan kelompok politik lain untuk memengaruhi hasil Pemilihan Umum 2024. Temuan dari artikel ini menunjukkan bahwa loyalitas pemilih Santri dan pesantren, dengan kesetiaan yang kuat, melampaui kelompok Abangan dan nasionalis. Oleh karena itu, peran dan pengaruh komunitas Islam dari pesantren di Jawa Timur memiliki posisi yang signifikan dan berpengaruh dalam dinamika politik selama Pemilihan Umum 2024.